Carrier dynamic and carrier Temperature in Quantum Well - Musa, Hiba J.; Flayyih, Ahmed H. (University of Thi-Qar Journal of Science, 2022)
Carrier temperature in quantum well (QW) semiconductor optical amplifier (SOA) has been studied,depending density matrix theory (DMT) and carrier dynamic in quantum well. The effect of volume carrier density, dopingon effect, pulse shape, nonradiative relaxation, and nonlinear gain coefficients on the carrier temperature and carrierheating has been investigated. The theoretical results show that; the time recovery increases straightforward withnonradiative recombination, where the relaxation time of nonradiative recombination reduces the rate of carrieroccupation in quantum states. Also, the carrier temperature increases with carrier density, free carrier absorption, carrierheating lifetime and reduces with pulse shape of pump pulses.